Exogenous Applications of Brassinosteroids Improve Color of Red Table Grape (Vitis vinifera L. Cv. “Redglobe”) Berries - Vergara, Alexis E.; Díaz, Katy; Carvajal, Rodrigo; Espinoza, Luis; Alcalde, José A.; Pérez-Donoso, Alonso G. (Frontiers in Plant Science, 2018)
Color and other quality parameters of “Redglobe” grape (Vitis vinifera L.) berries were evaluated after treatment with brassinosteroid (BR) analogs. Three BRs analogs (24-epibrassinolide, Triol, or Lactone) were applied at three concentrations (0.0, 0.4, or 0.8 mg⋅L-1), at the onset of veraison. A commercial formulation (B-2000®) was also applied, at a recommended rate of 0.06 mg⋅L-1. The tested BR analogs were effective improving berry color (evaluated as color index for red grapes, CIRG), increasing the levels of soluble solids and anthocyanins, and changing the types of anthocyanins present without altering other quality and yield parameters. The effects of BR analogs on color enhancement could be explained by an increase in soluble solids content and/or anthocyanin content. Treatment with 24-epibrassinolide (at 0.4 mg⋅L-1) or the commercial formulation tended to favor the production of dihydroxylated anthocyanins, which are responsible for the red and pink colors of grape berries. Results indicate that the use of BRs constitutes a potential tool in the production of table grapes. This is the first report of this enhancement effect in a productive context.